Risk Factors for Severe Malaria and Implementation of the New Malaria Vaccine in Children Under-5 Years: A Narrative Review - Vivian O. Onukwuli; Wilfred C. Ukemenam; Kenechukwu K. Iloh; Beckie N. Tagbo (International Journal of Medicine and Health Development, 2025)
Malaria has remained a major global health challenge, particularly in sub-Saharan Africa, where young children, especially those under-5 years, are vulnerable. Mortality from malaria results mainly from the severe forms of the disease and several risk factors are known to increase the susceptibility of the under-fives to severe malaria. A literature search was conducted using PubMed, Google Scholar, and reference lists of relevant articles published in English between 2008 and 2023. Studies addressing the link between obesity and periodontal disease were selected, critically reviewed, and synthesized in a narrative format. Malaria is preventable and treatable. Improvements in its control interventions have resulted in considerable reductions in morbidity and mortality associated with malaria in parts of Africa. However, malaria continues to pose a significant public health threat. The newly introduced malaria vaccine, when deployed in combination with other current malaria control tools, could play an essential role in reducing the prevalence of malaria and ultimately improve the morbidity and mortality from this reemerging infectious disease. Implementing a malaria vaccine in children in sub-Saharan Africa is a critical public health intervention. This work reviewed the risk factors for severe malaria and analyzed the prospects and challenges of implementing a malaria vaccine, which holds great promise for reducing the burden of this deadly disease in children under-5 years.